Rosuvastatin ameliorates obesity-associated insulin resistance in high-fat diet-fed mice by modulating the gut microbiota and gut metabolites - Yao, Chao; Xue, Xin; Jia, Yunxi; Li, Min; Zhang, Lu; Yuan, Hong; Xue, Huiting; Hu, Ruiping (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionInsulin resistance (IR) underlies metabolic diseases such as obesity and diabetes. Statins are lipid-lowering drugs that have also been studied to improve insulin resistance, but the mechanism is not well understood. Metagenomics and metabolomics were used to analyze the main species and metabolic pathways involved in intestinal microbes while improving insulin resistance in mice with rosuvastatin in this study.MethodsC57BL/6J male mice fed a high-fat diet were used to establish the insulin resistance (IR) mouse model. Rosuvastatin (RSV) was then administered for 8 weeks. Metagenomics and metabolomics were utilized to analyze the microbial composition and short chain fatty acid metabolites in intestinal feces of mice.ResultsIt was observed that insulin-resistant mice showed significant improvement in insulin resistance following treatment with RSV. In comparison to the HFD group, specific bacterial strains were significantly increased, and the levels of butyric acid, caproic acid, and isovaleric acid among the short-chain fatty acids were notably elevated in the RSV group. Through KEGG enrichment analysis, 19 dominant strains and 15 key enzymes involved in butyric acid metabolism were identified.ConclusionsThe results suggested that IR mice might enhance insulin sensitivity by promoting butyric acid synthesis via intestinal microbes following RSV treatment.